Pembuatan Buku Pedoman Penggunaan Eprints bagi Pustakawan di Perpustakaan Universitas Dharma Andalas Padang - Putri, Vebriana; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed about the steps in making handbook of Eprints use for for librarians at the Library of Dharma Andalas University in Padang. The aim of this paper is to describe how to make handbook of Eprints use for librarians at the Library of Dharma Andalas University, Padang. The method used in this paper is descriptive, the retrieval of data is collected by two ways, namely observation and direct interview. Based on the research results, it can be concluded that the steps in making handbook of Eprints use for librarians at Library of Dharma Andalas University, as follow: (a) needs analysis, the author interviews the librarians at the Library of Dharma Andalas University to obtain the information as what book that the librarian wants, so that the product will be in accordance with librarians’ needs and it can attract the librarians to read it; (b) the design of products, the author made the design of product and its parts in the handbook, in the form of a chart; (c) making of the product, after the author made the design, the next step is making the products based on librarians’ needs at Library of Dharma Andalas University.There are two steps being taken to make the product. First, collecting the data and information through interviews and observation directly. Second, making a framework for writing that contains the basic provisions of a topic that should be developed.Keywords: Eprints Program; Handbook of Eprints use